2013
DOI: 10.1258/ar.2012.120405
|View full text |Cite
|
Sign up to set email alerts
|

Early results of real-time qualitative sonoelastography in the evaluation of parotid gland masses: A study with histopathological correlation

Abstract: Although sonoelastography seems to be promising in the differentiating of low-grade malignancies, the primary role of radiology is currently limited to determination of localization, size, and morphology of parotid tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…The technique has been used to assess the hardness of various normal and abnormal tissues, [1][2][3][4][5][6] and to differentiate malignant from benign lesions in the breast, prostate, thyroid, lymph nodes and salivary glands. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ultrasound elastography uses either strain or shear wave velocity. 25,26 In strain elastography, tissue strain induced by compression with the probe is used as an indicator of hardness.…”
Section: Introductionmentioning
confidence: 99%
“…The technique has been used to assess the hardness of various normal and abnormal tissues, [1][2][3][4][5][6] and to differentiate malignant from benign lesions in the breast, prostate, thyroid, lymph nodes and salivary glands. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ultrasound elastography uses either strain or shear wave velocity. 25,26 In strain elastography, tissue strain induced by compression with the probe is used as an indicator of hardness.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] These reports indicated an especially variable appearance of pleo- morphic adenomas on elastography. [6][7][8]10 Although benign tumors other than pleomorphic adenomas appeared softer in qualitative elastographic studies, some appeared softer and others harder.…”
Section: Discussionmentioning
confidence: 88%
“…[6][7][8]10 Although benign tumors other than pleomorphic adenomas appeared softer in qualitative elastographic studies, some appeared softer and others harder. 4,8,9 In a study by Bhatia et al, 6 pleomorphic adenomas appeared stiffer than other benign parotid gland tumors, with a wide distribution of maximum elasticity values (range, 16.4-214.8 kPa). 6 These data show that SWE cannot differentiate benign parotid gland tumors from malignant counterparts by measurement of the maximum shear elastic modulus.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Because many diseases correlate with changes in the mechanical properties of tissues, this technique has been successfully applied in detecting and assessing various pathologies of thyroid gland, breast, lymph nodes, major salivary gland, prostate, kidney, and liver [1][2][3][11][12][13][14][15][16][17]. However, to our knowledge, no study has been reported previously in the medical literature using real time sonoelastography to assess gallbladder polyps.…”
Section: Discussionmentioning
confidence: 99%